Regionalni vidiki inoviranja kot osnova konkurenčnosti podjetja znotraj države in EU - Markič, Mirko (Strojniški vestnik, 2006)
In 2000 the European Council approved the Lisbon strategy, which represents a long-term strategy with the aim to make the EU the most competitive, dynamic knowledge-driven economy in the world by 2010. Since Europe is a group of countries with different degrees of economic and research development, languages, social conditions, history, culture, etc., it is thus essential to preserve and develop a strong regional component together with a comprehensive approach to managing the EU. This is true not only for the statesbut also for the regions. At the same time, in its documents the EU set fostering innovativeness among its priorities. In this paper we thus wish to describe the opportunities for Slovenia in this extremely important segment - regional orientation of the innovative processes. On the basis of an analysis of the innovative processes in Slovenia and the EU we created a model of innovation processes in three steps. In the first one we define what the region has to achieve in order to become innovative. Fundamental guidance for the development is the modernization of deliberation and the performance reconciliation of all participants regarding innovation, which is the foundation for an improvement of competitiveness as well as a better quality of life of its inhabitants and society as a whole. In the second step we define how we should act within specific regional circumstances, taking into consideration a dialectic system of conditions for achieving innovation withinthe company or other organisations and the characteristics of the regionin broader criteria. In the third step we connect on one side the regionand its activities with a company and other organisations, and on the other side with Republic and European development guidelines and establish a connection with an innovation support environment.
Keywords: konkurenčnost podjetij; procesi inovacijski; modeli; okolje podporno; strategije regijske; konkurenčnost; inovativnost